2015
DOI: 10.1093/cvr/cvv260
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte exosomes regulate glycolytic flux in endothelium by direct transfer of GLUT transporters and glycolytic enzymes

Abstract: These findings establish CM-derived exosomes as key components of the cardio-endothelial communication system which, through intercellular protein complementation, would allow a rapid response from ECs to increase glucose transport and a putative uptake of metabolic fuels from blood to CMs. This CM-EC protein complementation process might have implications for metabolic regulation in health and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(121 citation statements)
references
References 49 publications
3
117
0
1
Order By: Relevance
“…Gene Ontology (GO) analysis of exosome cargo identified the molecules, which alters the angiogenic activity of the endothelial cells. In glucose deprived medium, the exosomes were identified to be loaded with functional glucose transporters and glycolytic enzymes, which are internalized by ECs to increase glucose uptake, glycolytic activity, and pyruvate production in recipient cells 27,109 . A paracrine miRNA crosstalk between cardiac fibroblasts (CFs) and cardiomyocytes (CMs) was found to be mediated by the CF secreted miRNA-enriched exosomes.…”
Section: Therapeutic Effects Of Exosomes Derived From the Differenmentioning
confidence: 99%
“…Gene Ontology (GO) analysis of exosome cargo identified the molecules, which alters the angiogenic activity of the endothelial cells. In glucose deprived medium, the exosomes were identified to be loaded with functional glucose transporters and glycolytic enzymes, which are internalized by ECs to increase glucose uptake, glycolytic activity, and pyruvate production in recipient cells 27,109 . A paracrine miRNA crosstalk between cardiac fibroblasts (CFs) and cardiomyocytes (CMs) was found to be mediated by the CF secreted miRNA-enriched exosomes.…”
Section: Therapeutic Effects Of Exosomes Derived From the Differenmentioning
confidence: 99%
“…In mice in vivo angiogenesis was increased in implanted matrigel plugs loaded with endothelial cell-derived exosomes but not in plugs loaded with exosomes isolated from antagomir-treated endothelial cells.[38] CardiomyocytesHL-1 cell lineExosomesNot determinedGrowth factor (TGF-β2, PDGF-BB) treatment affected messenger RNA contents of exosomes secreted by cardiomyocytes. No function reported.[26] CardiomyocytesRat (neonatal)ExosomesGLUT1, GLUT4Glucose deprivation of neonatal rat cardiomyocytes increased production of exosomes carrying GLUT1 and GLUT4 transporters which were transferred to rat cardiac microvascular endothelial cells to stimulate uptake of glucose and glycolysis.[27] CardiomyocytesH9C2 cell lineExosomesNot determinedGlucose deprivation increases production of exosomes in cardiomyocytes which can be transferred to HUVECs and induce transcriptional changes, proliferation and tube formation in vitro. Differential protein and miRNA content demonstrated under normal conditions or glucose deprivation which may account for these effects.[28] PlateletsHumanMicroparticlesLipid growth factorsIncreased survival, proliferation and migration of HUVECs reduced by treatment with activated charcoal suggesting involvement of lipid growth factor mediators.[19] PlateletsHumanMicroparticlesVEGF, bFGF, PDGF, heparanaseStimulation of sprouting angiogenesis in a rat aortic ring model.…”
Section: Introductionmentioning
confidence: 99%
“…The protein and mRNA content of their exosomes varies under different culture conditions and stimulus such as oxidative stress [24, 26]. Under conditions of oxidative stress or glucose deprivation, neonatal cardiomyocytes and cardiac-like H9c2 cells release increased numbers of exosomes [27]. In co-culture with endothelial cells, these exosomes induced endothelial proliferation and angiogenesis as well as increasing glucose uptake and glycolytic activity in recipient cells [27, 28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, communication between cardiomyocytes and endothelial cells would be essential for efficient regulation of substrate delivery. Indeed, a recent study has identified cardiomyocyte-derived exosomes loaded with glucose transporters and glycolytic machinery components as key in allowing for a rapid response from the endothelium in the coordinated regulation of glucose uptake by the heart [152]. Similar mechanisms may govern cardiac FA uptake and use.…”
Section: Perspectivesmentioning
confidence: 99%